2018
DOI: 10.1155/2018/6254929
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum and Auricularia polytricha Mushrooms Protect against Carbofuran‐Induced Toxicity in Rats

Abstract: The current study aimed to investigate the ameliorative effects of two types of mushrooms, Ganoderma lucidum (GL) and Auricularia polytricha (AP), against carbofuran- (CF) induced toxicity in rats. Male Wistar rats (n = 42) were divided into six equal groups. The rats in the negative control group received oral administration of CF at 1 mg/kg with the normal diet for 28 days. The treatment groups received oral administration of ethanolic extract of GL or AP at 100 mg/kg followed by coadministration of CF at 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Carbofuran (2, 3-dihydro-2,2-dimethyl-7-benzofuranyl-N methyl carbamate) is one of the common pesticides that is used to eradicate pests, such as insects, mites, and nematodes in the soil [1–3]. This pesticide is commonly used in agricultural and household [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Carbofuran (2, 3-dihydro-2,2-dimethyl-7-benzofuranyl-N methyl carbamate) is one of the common pesticides that is used to eradicate pests, such as insects, mites, and nematodes in the soil [1–3]. This pesticide is commonly used in agricultural and household [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The mobile phase was composed of solvent A (HPLC grade methanol with 0.1 percent phosphoric acid) and solvent B (HPLC grade water with 0.1 percent phosphoric acid). The following technique was performed to obtain the elution of the column: from 0 to 10 minutes, the concentration of solvent B grew from 35% to 55%; from 10 to 25 minutes, the concentration of solvent B increased to 62 percent; from 25 to 30 minutes, the concentration of solvent B increased to 85 percent; and the final composition remained constant until 35 minutes [ 31 ]. The solvents utilized were of HPLC grade.…”
Section: Methodsmentioning
confidence: 99%
“…Auricularia mushrooms have been reported to have antiviral [4], antitumoral [5,6], and immune-enhancing activities [7]. Many Pharmaceuticals 2021, 14, 1001 2 of 19 studies have shown that Auricularia polytricha (AP) contained antioxidant compounds [8][9][10][11]. Aqueous extracts of AP have attenuated paracetamol-induced hepatotoxicity and hepatic lipid accumulation in rat models due to their antioxidative effects [12,13].…”
Section: Introductionmentioning
confidence: 99%